A Giant Trigeminal Schwannoma, Posterior Fossa and Middle Fossa Extradural Approach: A Case Report (Bangladesh Journal of Neurosurgery, 2020)
Trigeminal schwannomas are rare tumors that are located in the posterior and middlecranial fossae in about a quarter of the cases. The presentation pattern is differentaccording to the involved compartment and the goal of surgery is complete removal.We present the case of a 28-years old man who presented with a left sided trigeminalschwannomas extending from the posterior to the middle fossa. Middle fossa part ofthe tumour was removed by extradural subtemporal approach and posterior fossapart was removed by retrosigmoidretromastoid approachBang. J Neurosurgery 2020; 9(2): 162-167